Investigation of lichen populations and their similarity analysis in Serif Yuksel Forest, Turkey - (:unkn) unknown (TRIVENI ENTERPRISES, 2010)
Sorensen similarity indices of lichen species in Serif Yuksal forest ranged between 0.29 and 0.84. A linear relation was found between species number sum of two lichen populations and their similarity indices, The linear equation is Y=0.0076x + 0.1467 and the R-2 of the equation is 0.2476 which is significant at p<0.001, There has been identified a linear relation between the average similarity index of the sites and fir participation percentage. The obtained equation is Y=0,0009x+0,5271 and the R-2 of the equation is 0,2853 which is significant at p<0.002. In the pure fir stands there has been found a linear relation between the altitude difference and similarity index, The obtained equation is Y=-0.0011x + 0.6962 and the R-2 of the equation is 0.1755 which as significant at p<0.001.
Keywords: Sorensen similarity index; Attitude; Bolu; Lichen; MICROFUNGAL COMMUNITY STRUCTURE